Successful treatment of severe Clostridium difficile infection by administration of crushed fidaxomicin via a nasogastric tube in a critically ill patient. (February 2017) - Arends, Sven; Defosse, Jerome; Diaz, Cori; Wappler, Frank; Sakka, Samir G.
Highlights: We report a case of a 79-year old patient who developed septic shock with increasing need of norepinephrine and acute renal failure due to a severe Clostridium difficile infection. Antimicrobial therapy with vancomycin via a nasogastric tube and metronidazole i.v. did not lead to improvement, infection parameters further increased and the clinical condition impaired. After 10 days antimicrobial therapy was changed to fidaxomicin, crushed and administered via nasogastric tube. Within 24 hours, infection parameters decreased. Further diarrhoea ceased and stool samples were negative for Clostridium difficile antigen. Abstract: Objective: To report the successful use of crushed fidaxomicin via a nasogastric tube for treatment of a severe Clostridium difficile infection in a critically ill patient. Data Sources: Clinical observation of a patient, images of abdominal computed tomography, antimicrobial therapy and course of infection parameters. Data Extraction: Relevant information contained in the medical observation of the patient and selection of image and laboratory parameters performed in the patient. Data Synthesis: We report a case of a 79-year old patient who developed septic shock with an increasing need for norepinephrine and acute renal failure due to a severe Clostridium difficile infection. Antimicrobial therapy with vancomycin via a nasogastric tube and metronidazole i.v. did not lead to improvement, infection parameters further increased, and the clinical condition became increasingly impaired. After 10 days, antimicrobial therapy was changed to fidaxomicin, crushed and administered via nasogastric tube. Within 24 hours, infection parameters decreased. Further diarrhoea ceased and stool samples were negative for Clostridium difficile antigen. Conclusions: Our case confirms that administration of fidaxomicin via a nasogastric tube was safe and effective in this patient. Further studies are needed to evaluate the efficacy of this strategy in critically ill patients systematically.